Thyroid Nodules Diagnosis and Management (Contemporary Endocrinology,, 2018)
Utilizing the most current evidence, this practical book is the first publication of its kind to focus exclusively on the clinical and laboratory evaluation and therapy of thyroid nodules, including advances in evaluation and controversies in management. Opening with chapters presenting the epidemiology, history, laboratory and clinical evaluation of thyroid nodules, the use of radioactive isotope ultrasound and CT scanning in diagnosis is then described. The interpretation of thyroid cytology following fine needle aspiration (FNA) biopsies and the use of molecular markers are discussed in detail, as is the controversial use of thyroxine therapy. Following a presentation of the common and minimally invasive surgical approaches to thyroid nodules, chapters on multinodal goiters, incidentalomas and thyroid nodules in children round out the presentation. Written and edited by leading US and international thyroidologists, Thyroid Nodules is a useful, state-of-the-art text for endocrinologists, surgeons, and primary care physicians.